(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
The rapid growth of cultural tourism presents a critical dilemma for nations across Asia and Africa. Framed by the enduring legacy of the 1955 Bandung Conference, which championed South-South solidarity and cultural sovereignty, this paper interrogates the dualistic nature of cultural tourism as both a potential vehicle for nationbuilding and an instrument of neocolonialism. The paper employs a critical review of stakeholder analysis to establish the power dynamics inherent in the tourism ecosystem, identifying how economic benefits, cultural representation, and political agency are distributed among local communities, domestic and international tourists, governments, and multinational corporations. It argues that the Bandung Spirit’s principles of mutual respect, sovereignty, and cooperative advancement provide an essential ethical framework for contemporary tourism development. The model prioritizes domestic tourism, intellectual property rights over cultural heritage, and equitable benefit-sharing as essential pillars for decolonizing tourism. It is concluded that cultural tourism, when consciously realigned with the Bandung ethos, can transcend its neocolonial pitfalls to become a genuine form of reciprocal cultural exchange and sustainable economic development, fostering a renewed spirit of solidarity in the modern era.